The Effect of the Governance Environment on Marketing Channel Behaviors: The Diamond Industries in the U.S., China, and Hong Kong - Li, Shaomin ca. 20./21. Jh. (Journal of business ethics, 2009)
International differences in how market exchanges are conducted (e.g., the mode of entry, level of ownership, and conflict resolution) have been attributed mainly to national culture and cultural distance. However, the cultural arguments cannot explain why economies/countries with similar cultural backgrounds (e.g., Hong Kong and China) exhibit differences in exchange arrangements. Thus, the cultural arguments provide little strategic guidance to multinational corporations (MNCs) in international marketing. We propose that in addition to culture, the governance environment in a country, namely, the political, economic, and social institutions that facilitate or constrain the choice of governance mechanisms, influences the way organizations conduct market exchanges. This important factor heretofore has been ignored. Specifically, we introduce a typology of rule-based and relation-based governance environment to explain how the environment affects marketing channel behaviors, such as barriers to entry, channel exclusivity, information access, trust, and dispute resolution. We analyze the diamond industry in the rule-based governance environment in the U.S. and in the relation-based governance environment in China, and using the diamond industry in Hong Kong as a validation, to develop theoretical propositions and strategic implications for MNCs.